Abbreviations in The Comment Column of The Tribunnews Account on Tiktok - Widodo, Joko; Budi Qur’ani, Hidayah; Rahma Wijaya Putra, Candra (Riviera Publishing, 2023)
One application that is currently in vogue is TikTok. One of the news media that utilizes the TikTok platform is Tribunnews. This news site provides various news that occurs in both local, national, and international news in a precise and fast manner. Tribunnews provides a forum for the community to share information or convey ideas and empirical experiences that benefit the nation's life through two Tribunnews sections, namely Tribuners and Citizen Reporter. Research related to abbreviation analysis in the comment column of the Tribunnews account on Tiktok is essential to improve readers' understanding, especially students. This research uses descriptive methods with qualitative research types. The data source for this research is the Tribunnews account on Tiktok from June 28, 2021, to July 22, 2021. This research data is in the form of words, phrases, clauses and sentences containing types, forms of origin, and factors forming abbreviations in the comments on the Tribunnews account on Tiktok. The data analysis technique was carried out by reading the comments of the Tribunnews account on Tiktok, identifying data, classifying, and connecting the data with existing theories. Abbreviations dominate the most when compared to other types. In the original form of abbreviations, noun phrases, proper names, and words are found. The noun phrase origin form dominates when compared to other origin forms. In the abbreviation formation, factors found in the Tribunnews account on Tiktok are preserving/retaining the first letter of each component, preserving/retaining the first syllable, and preserving/retaining some syllables.